Risk of juvenile idiopathic arthritis among children conceived after fertility treatment: a nationwide registry-based cohort study. Issue 6 (30th March 2019) - Sperling, C D; Kjaer, S K; Hargreave, M; Jensen, A
Abstract: STUDY QUESTION: Is the risk of juvenile idiopathic arthritis (JIA) increased in children conceived after fertility treatment, and is an observed association caused by specific types of fertility treatment or by factors associated with the underlying infertility? SUMMARY ANSWER: The risk of JIA in children conceived after fertility treatment (any and specific types of fertility treatment) was not convincingly affected when compared with children born to fertile women. WHAT IS KNOWN ALREADY: It has been suggested that fertility treatment may affect the development of the immune system and thereby increase the risk of developing autoimmune diseases, including JIA. STUDY DESIGN, SIZE, DURATION: This retrospective population-based cohort study included all live-born children in Denmark between 1 January 1996 and 31 December 2012 ( n = 1 084 184). The study population was followed from date of birth until first diagnosis of JIA as registered in the Danish National Patient Registry, date of 16th birthday, date of emigration, date of death or end of follow-up (31 December 2014), whichever occurred first. PARTICIPANTS/MATERIALS, SETTING, METHODS: The study cohort was linked to the Danish Infertility Cohort in order to identify children born to women with fertility problems ( n = 174 702) and fertility treatment ( n = 89 931). Cox proportional hazard regression models were used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) adjusted for potential confounders. MAIN RESULTS AND THE ROLE OF CHANCE: During a median follow-up period of 10.3 years, 2237 children were diagnosed with JIA. Children born to women with fertility problems had an increased risk of JIA (HR 1.18, 95% CI 1.05–1.32) compared with children born to fertile women. However, the risk was not increased in children conceived after any fertility treatment (HR 1.11; 95% CI 0.95–1.29), or after specific types of fertility treatment being ART (HR 1.05; 95% CI 0.83–1.33), IVF (HR 1.01; 95% CI 0.73–1.38), ICSI (HR 0.98; 95% CI 0.64–1.50) or any fertility drugs (HR 1.10; 95% CI 0.94–1.28) compared with children born to fertile women. The associations between fertility treatment and JIA were also assessed by using children born to women with fertility problems without fertility treatment in the index pregnancy as a reference group, however, the findings did not change substantially. LIMITATIONS REASONS FOR CAUTION: Despite a large study population, the statistical precision in some subgroup analyses may be affected due to the low number of JIA cases. There may be some misclassification of fertility problems, as some women have undiagnosed fertility problems and are therefore not included in the Danish Infertility Cohort; potentially leading to slight attenuation of the association between fertility problems and JIA. WIDER IMPLICATIONS OF THE FINDINGS: The results are based on national data and our findings can therefore be applied to other similar populations. Our results indicate that fertility treatment per se do not increase the risk of JIA but merely that the increased risk of JIA observed among children born to women with fertility problems may be due to underlying factors related to both infertility and JIA. However, as this is the first large study in this field, further studies are needed to confirm our findings. STUDY FUNDING/COMPETING INTEREST(S): The study was supported by grants from the Jascha Foundation, the Aase and Ejner Danielsens Foundation and The Danish Rheumatism Association. All authors report no conflicts of interest. TRIAL REGISTRATION NUMBER: N/A.